2012
DOI: 10.1155/2012/681875
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Incineration of Phenolic Compounds from the Hydrocarbon Industry Using Boron-Doped Diamond Electrodes

Abstract: Electrochemical incineration using boron-doped diamond electrodes was applied to samples obtained from a refinery and compared to the photo-electro-Fenton process in order to selectively eliminate the phenol and phenolic compounds from a complex matrix. Due to the complex chemical composition of the sample, a pretreatment to the sample in order to isolate the phenolic compounds was applied. The effects of the pretreatment and of pH on the degradation of the phenolic compounds were evaluated. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…Thus, an air-breathing MFC with a cathodic surface of 24 cm 2 made of carbon paper reached 0.268 A m -2 [35], while another one using carbon cloth with a layer of 0.1 mg cm −2 of Co plus wet-proofing, Nafion ant PTFE achieved 0.125 A m -2 [36] and another one with a 0.5 mg Pt cm -2 deposited on a 7 cm 2 cathode reached 0.429 A m -2 [26] . Better exerted current densities of about 2.12-2.83 A m -2 were obtained by using different catalysts such as Mn, Fe, Co, Ni [37], although these current densities were always lower than the attained in this work. Regarding the efficiency, it increases considerably from 0.04 % during the first days of start-up up to about 23 % at steady state regardless the load of Pt.…”
Section: Analytical and Electrochemical Measurementscontrasting
confidence: 54%
“…Thus, an air-breathing MFC with a cathodic surface of 24 cm 2 made of carbon paper reached 0.268 A m -2 [35], while another one using carbon cloth with a layer of 0.1 mg cm −2 of Co plus wet-proofing, Nafion ant PTFE achieved 0.125 A m -2 [36] and another one with a 0.5 mg Pt cm -2 deposited on a 7 cm 2 cathode reached 0.429 A m -2 [26] . Better exerted current densities of about 2.12-2.83 A m -2 were obtained by using different catalysts such as Mn, Fe, Co, Ni [37], although these current densities were always lower than the attained in this work. Regarding the efficiency, it increases considerably from 0.04 % during the first days of start-up up to about 23 % at steady state regardless the load of Pt.…”
Section: Analytical and Electrochemical Measurementscontrasting
confidence: 54%
“…In recent years, some combinations of electrochemical oxidation and photolysis had been reported by various researchers [8,9]. Most of these researchers concentrated on electro-Fenton technology in combination with UV irradiation, which may facilitate the photodecomposition of organic compounds, increase the generation of hydroxyl free radicals, and regenerate Fe 2+ from Fe 3+ species through a photoreduction mechanism [10][11][12][13]. However, there is little research on the combination of H 2 O 2 electrogeneration with direct photolysis in the absence of added catalysts such as Fe 2+ and TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, residues of low or high toxicity are mixed with each other, resulting in a residue of greater toxicity. Here, the phenol concentration, organic load, and dissolved solids are not comparable with any other residue, including wastewater from different refining processes [90]. The phenol concentration in the samples analyzed suggest that this residue cannot be treated by BO (a concentration >3,000 mg L −1 leads to the complete deactivation of the microorganisms).…”
Section: Characterization Of the Spent Causticsmentioning
confidence: 74%
“…When comparing the use of Ti/BDD with Ti/SnO 2 -Sb [87,88] and PbO 2 [89], it was found that the BDD electrode is much better for the destruction of phenol. Although the application of BDD in real samples has been weakly explored, when comparing the BDD with the electro-Fenton process for the treatment of wastewaters from refineries, it has been confirmed that even though the electro-Fenton process can induce a greater phenol degradation in comparison with the BDD electrode, the greater efficiency of degradation of the reaction byproducts (in terms of COD and TOC) occurs with BDD [9,90]. At the same time, other important studies applying the BDD for the treatment of water produced and typical wastewater from refineries have demonstrated the great efficiency of BDD [91][92][93].…”
Section: Introductionmentioning
confidence: 99%